THE PROSPECTS OF E-LEARNING IMPLEMENTATION IN EDUCATIONAL PROCESS OF MEDICAL UNIVERSITY - A. A. Kurmangulov; O. I. Frolova; S. V. Soloveva (Высшее образование в России, 2017)
The article considers the possibility and prospects of e-learning implementation in the educational process of future doctors and pharmacists. On the example of Tyumen State Medical University the authors show how the model ofe-learning platform can be implemented in the framework of a unified electronic educational environment of the University. The model of e-learning platform in the framework of full-time study medical specialties showed itself as a modern methodological basis for teaching and optimization of students' independent work, with the formation of cognitive strategies of self-learning and self-education as a basis and an integral part of future professional medical activity. The article demonstrates the application features of the main structural and functional elements of e-learning courses in medical school, adduces the examples of filling the theoretical, measurement and methodological blocks.